Lake ice and snow depth/thickness from Almbergasjön, 2017-11-13–2024-01-11 - Abisko Scientific Research Station (Swedish Polar Research Secretariat, 2026)
Observation of ice and snow depth and thickness of the SITES Water lakes.
Abisko Scientific Research Station (2026). Lake ice and snow depth/thickness from Almbergasjön, 2017-11-13–2024-01-11 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/M4PVBCMrP7VjbJwH9dYyA56X
Keywords: Abisko Scientific Research Station; Time instant; Time instant; Ice depth/thickness; Ice depth/thickness; Snow depth; Snow depth; Cover of snow on ice-covered lake; Cover of snow on ice-covered lake; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap